SENI URUTAN TRADISIONAL MELAYU: KEARIFAN TEMPATAN YANG KEKAL RELEVAN ATAU DIPINGGIRKAN? THE ART OF MALAY TRADITIONAL MASSAGE: IS LOCAL WISDOM REMAIN RELEVANT OR ALIENATED? - Mohd. Dahlan, Mohd. Fathul Khair; Shah Omar, Mardian (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract The art of traditional Malay massage is one element of local wisdom that should be given more attention. Various external influences increasingly taint such massages in Malaysia and to some extent changed the art itself. This study, therefore, aimed to identify the local community’s acceptance of traditional Malay massage and their openness in embracing local arts. The study also sought the public view on the future of traditional Malay massage. The paper, supported by the concept of human nature by Rousseau (1967), also collected responses from 200 respondents of various backgrounds through the distribution of online questionnaires. The study found that the traditional arts still have a place amongst the Malay community. Besides, it was proven that elements of external influences had been observed in traditional Malay massage. The implications of the study indicate that a concerted effort needs to be made to preserve this heritage art in order for it to remain relevant and produce more practitioners. Keywords: local wisdom, arts of traditional Malay massage, massage, concept of human nature.